PENGARUH PENGARUH PAJAK TANGGUHAN, TAX TO BOOK RATIO, LEVERAGE DAN SIZE TERHADAP KINERJA KEUANGAN PERUSAHAAN (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Periode Tahun 2013-2015) - Herrysen Suhendra, 12.05.52.0227; Wahyudi, Djoko (Students Journal of Accounting and Banking, 2016)
The purpose of this study was to analyze the effect of deferred taxes, the tax-to-book ratio, leverage and the size of the companys financial performance in companies listed on the Stock Exchange Year 2013-2015. The population in this study are all manufacturing companies listed in Indonesia Stock Exchange in the period 2013- 2015. The sample in this study as many as 48 companies. The sampling technique used purposive sampling. The criteria for the samples in this study were (1) Companies that earn taxable income in a row. It can be said the company has a good performance, because the profit for 3 consecutive years. (2) Companies that deliver complete data during the observation period from 2013 to 2015 relating to the variable (deferred taxes, the tax-to-book ratio, leverage, and size). The analysis tool used is multiple linear regression. The results of the analysis can be concluded that: Deferred tax is not significant positive effect on the financial performance of the company. Tax-to-book ratio and leverage significant negative effect on the financial performance. Size significant positive effect on the companys financial performance. Â Keywords:Â Tax-Deferred, Tax-To-Book Ratio, Leverage, Size, Financial Performance of Companies